Meta-Analysis of the Safety and Efficacy of α-Adrenergic Blockers for Pediatric Urolithiasis in the Distal Ureter - Sun, Fengze; Bao, Xingjun; Cheng, Dongsheng; Yao, Huibao; Sun, Kai; Wang, Di; Zhou, Zhongbao; Wu, Jitao (Frontiers in Pediatrics, 2022)
Abstract Objective: Pediatric urolithiasis is a common condition, and medical expulsive therapy has grown to be accepted by many parents. We carried out a meta-analysis to identify the efficacy and safety of α-adrenergic blockers for the treatment of pediatric urolithiasis.Methods: We identified related articles from the PubMed, Embase, and Cochrane Library databases. All published randomized controlled trials (RCTs) describing the use of α-adrenergic blockers and placebo treatment for pediatric distal urolithiasis were involved. The outcomes included stone expulsion rate, stone expulsion time, pain episodes, need for analgesia, adverse events, and related subgroup analyses.Results: A total of nine RCTs were involved in our study, including 586 patients. We found that α-adrenergic blockers could significantly increase the rate of stone expulsion (odds ratio [OR], 3.49; 95% confidence interval [CI], 2.38–5.12; P < 0.00001), reduce the stone expulsion time (mean difference [MD], −5.15; 95% CI, −8.51 to −1.80; P = 0.003), and decrease pain episodes (P < 0.00001) and analgesia demand (MD, −0.92; 95% CI, −1.32 to −0.53; P < 0.00001) but had a higher incidence of side effects (MD, 2.83; 95% CI, 1.55–5.15; P = 0.0007). During subgroup analyses, different medications (tamsulosin, doxazosin, and silodosin) also exhibited better efficiencies than placebo, except for doxazosin, which showed no difference in expulsion time . The three kinds of α-adrenergic blockers also appeared to be better tolerated, except for tamsulosin with its greater number of adverse events (MD, 2.85; 95% CI, 1.34¬–6.03; P = 0.006). Silodosin led to a better expulsion rate than tamsulosin (OR, 0.42; 95% CI, 0.20 to 0.92; P = 0.03). In addition, α-adrenergic blockers increased the stone expulsion rate regardless of stone size and decreased the expulsion time of stones measuring <5 mm , which was not the case for stones measuring >5 mm in expulsion time (MD, −3.61; 95% CI, −10.17 to 2.96; P = 0.28).Conclusion: Our review suggests that α-adrenergic blockers are well tolerated and efficient for treating pediatric distal urolithiasis. We also conclude that silodosin is the best choice of drug, offering a better expulsion rate, but it remains to be evaluated further by future studies.